Initial Psychometric Evaluation of the Barth Syndrome Symptom Assessment (BTHS-SA) for Adolescents and Adults in a Phase 2 Clinical Study - Chad Gwaltney; Alan Shields; Emily Love; Sarah Ollis; Jonathan Stokes; Iyar Mazar; Ethan Arenson; Anthony Aiudi; R. J. Wirth; Carrie Houts (Orphanet Journal of Rare Diseases)
Abstract Background Barth syndrome (BTHS) is a rare, X-linked disorder that stems from mutations in the TAFAZZIN (TAZ) gene with varying disease severity among patients. The Barth Syndrome Symptom Assessment (BTHS-SA) is a patient-reported outcome questionnaire developed to assess BTHS symptom severity. The current study reflects the first exploration of the assessment’s psychometric performance. Methods The BTHS-SA was administered in TAZPOWER, a phase 2, randomized, double-blind, placebo-controlled crossover study to evaluate daily subcutaneous injections of elamipretide in subjects with genetically confirmed BTHS. Descriptive and correlational analyses were used to assess the score distributions, reliability, and construct-related validity of BTHS-SA items and domains including a two-item (2 FS), three-item (3 FS), and four-item (4 FS) fatigue score, and a five-item myopathy score (5MS). Results Among the N = 12 white males (M age = 19.5, SD = 7.7) participating in the TAZPOWER trial, overall symptoms were rated as mild (n = 5, 41.7%), moderate (n = 5, 41.7%), severe (n = 1, 8.3%), or very severe (n = 1, 8.3%). Descriptive statistics for the BTHS-SA scores indicate variability of symptom severity both within symptom cluster and across patients. Promising results were found for both internal consistency (α = 0.67, 0.72, and 0.66 for the 3 FS, 4 FS, and 5MS, respectively) and test–retest reliability (ICC values ranging from 0.79 to 0.94 across two test–retest intervals). Correlational analyses showing moderate to strong relationships to other patient reports of fatigue (e.g., r = 0.59, 0.76, 0.68, and 0.61 between the PROMIS Fatigue SF and the 2 FS, 3 FS, 4 FS, and 5MS, respectively) and symptom severity (e.g., r = 0.60, 0.62, 0.56, 0.53 between a patient global rating and the 2 FS, 3 FS, 4 FS, and 5MS, respectively) support the measure’s convergent validity. A similar pattern of relationships was observed when correlating changes in BTHS-SA scores to reference measures, including moderate to strong relationships between the BTHS-SA and direct patient reports of change (r = 0.81, 0.79, 0.82, and 0.80 between a global impression of change score and the 2 FS, 3 FS, 4 FS, and 5MS, respectively). Conclusion Though the small sample size limits strong conclusions, this analysis suggests the BTHS-SA can produce reliable scores upon which valid inferences may be drawn. The BTHS-SA may be a useful tool to evaluate treatment benefits in this underserved population. Trial registration ClinicalTrials.gov identifier, NCT03098797. Registered 05 May 2017, https://www.clinicaltrials.gov/study/NCT03098797 .